The relationship between dyslipidemia and inflammation among adults in east coast China: A cross-sectional study - Hong, Najiao; Lin, Yongjun; Ye, Zhirong; Yang, Chunbaixue; Huang, Yulong; Duan, Qi; Xie, Sixin (Frontiers in Immunology, 2022)
This pilot study aimed to determine the relationship between prevalence of dyslipidemia and measured changes in the levels of proinflammatory cytokines and serum total antioxidant capacity in serum samples. A cross-sectional survey with purposive sampling of 2,631enrolled (age 18–85 years) was performed in the adult population of long-term residents of the municipality of East coast China in Fujian province between the year 2017 and 2019. Information was collected through a two-stage probability sampling design. Methods: The lipid profile was conducted by measuring the levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG). Dyslipidemia was defined according to ATP III diagnostic criteria. Serum parameters including IL-6/ TNF-a/ MCP-1, TBARS and TAC were measured in the consecutive times of three years. Familial history, education level, risk factors, etc. were determined. Association between dyslipidemia, and serum parameters were explored using multivariable logistic regression models. Sociodemographic, age, and risk factors were also investigated among all participants. Results: The mean prevalence of various dyslipidemia was: dyslipidemias 28.50%; hypercholesterolemia, 26.33%; high LDL-C, 26.10%; low HDL-C, 24.44%; and hypertriglyceridemia, 27.77%. A significant effect of aging was found among the all males and females. The mean levels of serum Il-6/TNF-a/MCP-1 were significant higher in all the types of dyslipidemia among males. Females with all types but low HDL-C showed an elevation of levels of IL-6 and MCP-1, and those with dyslipidemias and hypercholesterolemia presenting higher level of TNF-a compared to with the normal participants. The oxidative stress marker-TBARS increased among all types of dyslipidemia expect hypertriglyceridemia. All participants with different type of dyslipidemia had a lower total antioxidant capacity. Correlation analysis showed the cytokines and TBARS were positively associated with age, obesity, diabetes mellitus but not gender, sedentary leisure lifestyle, hypertension and CVD/CHD history. Activity of TAC was negatively associated the above parameters. Conclusions: A correlation between the prevalence of dyslipidemia and the modification of inflammation status was statistically significant. The levels of proinflammatory cytokines, oxidative stress and antioxidant capacity in serum may reflect the severity of the lipid abnormalities. These promising results warrant further a thorough medical screening.